2014
DOI: 10.1590/s1415-47572014000400003
|View full text |Cite
|
Sign up to set email alerts
|

Gender-dependent association of HSD11B1 single nucleotide polymorphisms with glucose and HDL-C levels

Abstract: In this study, we investigated the influence of two SNPs (rs846910 and rs12086634) of the HSD11B1 gene that encodes 11β-hydroxysteroid dehydrogenase type 1(11β-HSD1), the enzyme that catalyzes the conversion of cortisol to cortisone, on variables associated with obesity and metabolic syndrome in 215 individuals of both sexes from southern Brazil. The HSD11B1 gene variants were genotyped using the TaqMan SNP genotyping assay. Glucose, triglycerides, total cholesterol, HDL-cholesterol and LDL-cholesterol were me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 42 publications
(43 reference statements)
3
16
0
Order By: Relevance
“…In our study we restricted our analysis to obese women. Specific metabolic conditions associated with obesity and the influence of sex hormones, especially estrogen, on the lipid profile (Bataille et al ., 2005), can modulate the genetic polymorphisms' effect differently, as observed in previous studies (Ordovas, 2008; Tureck et al ., 2014; Locke,2015). …”
Section: Discussionsupporting
confidence: 55%
“…In our study we restricted our analysis to obese women. Specific metabolic conditions associated with obesity and the influence of sex hormones, especially estrogen, on the lipid profile (Bataille et al ., 2005), can modulate the genetic polymorphisms' effect differently, as observed in previous studies (Ordovas, 2008; Tureck et al ., 2014; Locke,2015). …”
Section: Discussionsupporting
confidence: 55%
“…On the basis of titles and abstracts, we selected 71 studies for full-text examination, of which 32 fulfilled the final inclusion criteria. Studies were grouped according to the relationship they set out to assess: 1) HSD11B1 gene expression in subcutaneous/visceral abdominal fat and MetS [ 6 - 8 ]; 2) HSD11B1 gene expression in subcutaneous/visceral abdominal fat and hyperglycemia [ 6 , 8 - 14 ]; 3) HSD11B1 gene expression in subcutaneous/visceral abdominal fat and obesity [ 4 , 6 - 11 , 13 , 15 - 28 ]; 4) HSD11B1 polymorphisms and obesity, MetS, or T2DM [ 29 - 37 ]. The main results of these studies are presented in Tables 1 , 2 , 3 and 4 .…”
Section: Resultsmentioning
confidence: 99%
“…In Europeans, association with MetS was found in Italian women, while a small study in Bosnians revealed correlations with BP, HOMA-IR and LDL cholesterol values [15,32]. Moreover, HSD11B1 gene appeared to influence glucose and HDL cholesterol level in Brazilian females of European descent [33]. Although data from adults do not confirm direct effect of HSD11B1 polymorphisms on body mass, an association with obesity and its measures (BMI, WC, waist-to-hip ratio) was reported in Spanish, American and Chinese children [20,21,23].…”
Section: Discussionmentioning
confidence: 93%